Fenomena Kepercayaan Terhadap Totem di Kec, Mappak, Tana Toraja: Studi Teologi Penciptaan dalam Alukta dan Kristen - Helianti Rande Manik (Melo: Jurnal Studi Agama-agama, 2021)
Torajanese in Mappak district, Tana Toraja, recognizes the belief system towards totem, which they called rindu. Rindu was believed as the twin of human but had the shape of animals. This belief was passed down across generations, by the followers of Alukta (tribal religion) and Christians. This research will analyze community perspectives about rindu, especially from the side of theology of creation. For the answers to these main questions, the researcher will use the phenomenology method. The result of this research showed that from the perspective of creation theology, Alukta and ritual aim to build the fraternity as the fellow creatures of God. However, from a Christian perspective, the concept of fraternity and worship is hard to be accepted. In other side, from the eco-theology concept, it gives a message about the importance to maintain the ecosystem sustainability and to minimize the environmental damage.   Orang Toraja di Kecamatan Mappak Tana Toraja mengenal sistem kepercayaan terhadap totem yang mereka sebut dengan rindu.  Rindu diyakini sebagai kembaran manusia tetapi dilahirkan dalam wujud binatang. Kepercayaan ini diwariskan lintas generasi, baik oleh penganut Alukta (agama suku) maupun mereka yang telah beragama Kristen. Dalam penelitian ini, penulis bermaksud mengkaji kepercayaan terhadap rindu untuk mengenali pemahaman masyarakat secara khusus dari segi teologi penciptaan. Peneliti menggunakan metode penelitian fenomenologi. Hasil penelitian menunjukkan, dari perspektif teologi penciptaan Alukta dan ritual yang dilakukan untuk membangun relasi persaudaraan sebagai sesama ciptaan. Namun dari perspektif teologi Kristen konsep persaudaraan dan penyembahan kepada rindu sulit diterima. Di sisi lain, dari segi ekotelogi terkandung pesan pentingnya menjaga keseimbangan ekosistem untuk meminimalisir kerusakan alam.